Estimation of the subsurface sedimentary structure of Amarapura township (Mandalay Region) based on microtremor survey. Issue 1 (October 2021) - Thein, P S; Kyaw, K M O; Kiyono, J; Pramumijoyo, S; Nu, T T; Khaing, K H; Than, W M; Win, T T; Thant, M
Abstract: In this study, we investigated the underground structure for Amarapura township, Mandalay region. One of the major structures in Myanmar is the Sagaing Fault system. Several powerful earthquakes have struck along the Sagaing Fault during recent years, one of the largest of which was an M 7.0 event that occurred on July 16, 1956 and caused several casualties. Following the event, we conducted a microtremor survey to estimate the shaking intensity distribution during the earthquake. Seven boreholes were drilled throughout the basin, especially in Amarapura township to evaluate the geotechnical properties of subsurface soil layers. The H/V analysis of the noise measurements reveals frequency peak values ranging from 0.5 to 3 Hz on the Amarapura township. The shear wave velocity becomes less than 190 m/s in some areas, which causes severe damage for buildings in high probability. The sediment thickness values range from less than 50 m to greater than 320 m on Amarapura township, Mandalay region. In this way, the accomplished work has contributed to the characterization of the underground structure and the identification of sites prone to amplify soil shaking during a possible strong earthquake.